A mountain of millipedes IX: Species of the family Gomphodesmidae from the Udzungwa Mountains, Tanzania (Diplopoda, Polydesmida) - Olsen, Sissel Anna; Rosenmejer, Trine; Enghoff, Henrik (European Journal of Taxonomy, 2020)
A new genus and six new species of the family Gomphodesmidae from the Udzungwa Mts are described, including Pogoro alopias Rosenmejer & Enghoff sp. nov., Pogoro siren Rosenmejer & Enghoff sp. nov., Pogoropsis prolixopes Rosenmejer & Enghoff gen. et sp. nov., Emphysemastix frampt Olsen & Enghoff sp. nov., Agrophogonus hamulus Olsen & Enghoff sp. nov., and Agrophogonus pusillokiellandi Olsen & Enghoff sp. nov. Emphysemastix dracarys Olsen & Enghoff sp. nov. from Iringa city is described. Descriptive notes are given for Pogoro scharffi Hoffman, 2005, and Agrophogonus mwanihana Hoffmann, 2005. General gomphodesmid gonopod morphology is described and illustrated. A key to Udzungwa gomphodesmids is presented, as well as revised keys to all species of Emphysemastix and Agrophogonus. All gomphodesmid species from the Udzungwa Mts are mapped.